(untitled) (Transport systems and technologies, 2020)
The methods of calculation of steering systems of vehicles are analyzed. The main factors that influence the driver’s efforts when turning steered wheels are identified. They depend on the design of the steering, the trajectory of movement, speed, mass. It is determined that on surfaces with high coefficient of adhesion when turning the steered wheels in place, a significant part of the moment of resistance when turning the wheels is the moment of resistance of the tire rotation. Reducing the torque of the tire occurs while driving, which in turn reduces the overall torque of the steered wheels. The characteristic of the moment of resistance of the rotation of the tire is non-linear, which complicates the calculation. Therefore, for the calculation of the characteristic is divided into sections with conditionally the same dependence. The dependence of the moment of resistance of the rotation of the tire on the spot on the angle of rotation of the steered wheel of the trolleybus with the maximum allowable load on the axle was obtained. The dependence of the driver’s effort on the moment of resistance on the steered wheels is shown. The mechanical parameters of the electric power steering of the trolleybus are determined.